Substrate-Dependent Functional Alterations of Seven CYP2C9 Variants Found in Japanese Subjects - Maekawa, Keiko; Harakawa, Noriko; Sugiyama, Emiko; Tohkin, Masahiro; Kim, Su-Ryang; Kaniwa, Nahoko; Katori, Noriko; Hasegawa, Ryuichi; Yasuda, Kazuki; Kamide, Kei; Miyata, Toshiyuki; Saito, Yoshiro; et al. (Drug metabolism and disposition, 2009)
CYP2C9 is a polymorphic enzyme that metabolizes a number of clinically important drugs. In this study, catalytic activities of seven alleles found in Japanese individuals, CYP2C9*3 (I359L), *13 (L90P), *26 (T130R), *28 (Q214L), *30 (A477T), *33 (R132Q), and *34 (R335Q), were assessed using three substrates (diclofenac, losartan, and glimepiride). When expressed in a baculovirus-insect cell system, the holo and total (apo and holo) CYP2C9 protein expression levels were similar among the wild type (CYP2C9.1) and six variants except for CYP2C9.13. A large part of CYP2C9.13 was present in the apo form P420. Compared with CYP2C9.1, all variants except for CYP2C9.34 exhibited substrate-dependent changes in Km, Vmax, and intrinsic clearance (Vmax/Km). For diclofenac 4′-hydroxylation, the intrinsic clearance was decreased markedly (by >80%) in CYP2C9.13, CYP2C9.30, and CYP2C9.33 and variably (63–76%) in CYP2C9.3, CYP2C9.26, and CYP2C9.28 due to increased Km and/or decreased Vmax values. For losartan oxidation, CYP2C9.13 and CYP2C9.28 showed 2.5- and 1.8-fold higher Km values, respectively, and all variants except for CYP2C9.34 showed >77% lower Vmax and intrinsic clearance values. For glimepiride hydroxylation, the Km of CYP2C9.13 was increased 7-fold, and the Vmax values of all variants significantly decreased, resulting in reductions in the intrinsic clearance by >80% in CYP2C9.3, CYP2C9.13, CYP2C9.26, and CYP2C9.33 and by 56 to 75% in CYP2C9.28 and CYP2C9.30. These findings suggest the necessity for careful administration of losartan and glimepiride to patients bearing these six alleles.